Anti-Inflammatory Effects of Weissella cibaria SDS2.1 Against Klebsiella pneumoniae-Induced Mammary Gland Inflammation - Meiyi Ren; Tianxiong Jin; Jingdi Tong; Deyuan Song; Qinna Xie; Xiaohan Li; Yan Li; Kangping Liu; Jian Gao; Mingchao Liu; Jia Cheng (Animals)
Dairy cows are highly susceptible to mastitis caused by Klebsiella pneumoniae, and treating these infections poses a challenge due to the resistance of the bacterium to common antibiotics. This study aimed to evaluate the safety of W. cibaria SDS2.1 and investigate its protective effects against K. pneumoniae-induced mastitis. The safety of W. cibaria SDS2.1 was assessed through comprehensive analyses, including antibiotic resistance profiling, hemolysis assays, cell cytotoxicity tests, and whole-genome sequencing. Furthermore, its ability to protect against cellular and tissue damage caused by K. pneumoniae-induced mastitis was evaluated using both in vitro and in vivo models. Our results revealed that W. cibaria SDS2.1 was non-hemolytic, non-cytotoxic, and significantly inhibited the growth of K. pneumoniae (p < 0.05). Additionally, W. cibaria SDS2.1 effectively reduced the adhesion and invasion of K. pneumoniae. In the K. pneumoniae-induced mouse mastitis model, W. cibaria SDS2.1 significantly reduced myeloperoxidase (MPO) activity, mammary tissue damage, and the expression of inflammatory cytokines (IL-6, IL-1β, and TNF-α) (p < 0.05). In K. pneumoniae-infected bovine mammary epithelial cells (bMECs), W. cibaria SDS2.1 significantly decreased lactate dehydrogenase (LDH) release, indicating reduced cellular damage. These findings demonstrate that W. cibaria SDS2.1 exhibits anti-inflammatory properties in experimental models, suggesting its potential role in mitigating K. pneumoniae-induced mastitis.